(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article explores innovative pedagogical approaches for forming a historical worldview among university students. It emphasizes the role of digital technologies, critical thinking, and interactive learning methods in developing historical consciousness. The study also examines the integration of virtual reality, project-based learning, and interdisciplinary strategies in modern history education. The findings highlight that innovation in teaching history not only strengthens students’ analytical and cultural understanding but also enhances civic responsibility and global awareness.